Rio bravo [videorecording (DVD)] - Hawks, Howard, 1896-1977; Wayne, John, 1907-1979; Martin, Dean, 1917-1995; Nelson, Rick, 1940-1985; Dickinson, Angie; Brennan, Walter, 1894-1974; Bond, Ward, 1903-1960 (Warner Bros. Entertainment : Distributed by Warner Home Video, 2010)
On one side is an army of gunmen dead-set on springing a murderous cohort from jail. On the other is Sheriff John T. Chance and his two deputies: one a recovering drunkard, the other a crippled codger. Also in their ragtag ranks are an unseasoned, trigger-happy youth and a woman with a past-- and her eye on Chance.